2013
DOI: 10.1371/journal.pone.0083161
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with a Thermostable Newcastle Disease Virus K148/08 Strain Originated from Wild Mallard Duck Confers Protection against Lethal Viscerotropic Velogenic Newcastle Disease Virus Infection in Chickens

Abstract: Newcastle disease (ND) is one of the most devastating poultry infections because of its worldwide distribution and accompanying economical threat. In the present study, we characterized the ND virus (NDV) K148/08 strain from wild mallard duck, with regard to safety, thermostability, immunogenicity, and protective efficacy against velogenic ND viral infection. The NDV K148/08 strain offered enhanced immunogenicity and safety relative to commercially available vaccine strains. The NDV K148/08 strain was safe in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…In our study, we attempted to identify a local immunoprotective vaccine against the infection of the circulating genotype. Wild waterfowl have been known to be reservoirs of avirulent and low-virulent NDV strains that provide immunogenic and protective profiles (Shim et al, 2011;Jeong et al, 2013). In our case, all the previous LBM APMV-1 isolates were highly virulent, but waterfowl APMV-1 isolates were confirmed low-virulent by biological and molecular methods of the fusion protein cleavage site (Collins et al, 1993;Byarugaba et al, 2014).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In our study, we attempted to identify a local immunoprotective vaccine against the infection of the circulating genotype. Wild waterfowl have been known to be reservoirs of avirulent and low-virulent NDV strains that provide immunogenic and protective profiles (Shim et al, 2011;Jeong et al, 2013). In our case, all the previous LBM APMV-1 isolates were highly virulent, but waterfowl APMV-1 isolates were confirmed low-virulent by biological and molecular methods of the fusion protein cleavage site (Collins et al, 1993;Byarugaba et al, 2014).…”
Section: Discussionmentioning
confidence: 56%
“…The ICPIs and IVPIs of three isolates remained at <0.44 and 0.00, respectively, throughout the passages except for the IVPI of 0.05 for NDV-178/UG/MU/ 2011. Altogether, these viruses were of low-virulent strains that can be used for immunization tests in bird studies (Jeong et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Control is normally achieved by the use of live and inactivated vaccines [54]. Haemagluttination inhibition titres were traditionally used to confirm protection against NDV challenge [55,56], and the mean NDV HI titre in both single and combined vaccinated groups described here were >5.63 log 2 , which is above the protective titre against virulent NDVs [19,23,57,58]. Current work showed that simultaneous vaccination of NDV + H120 + CR88 in commercial broiler chicks does not interfere with the induction of protective immunity against NDV.…”
Section: Ibv Ampvmentioning
confidence: 79%
“…The I-2 seed strain is produced by the Australian Centre for International Agricultural Research and provided to countries for the production of ND vaccines for village poultry flocks (Copland and Alders, 2005). Progress in identifying and characterizing other thermostable and immunogenic NDV strains continues (Jeong et al, 2013). These vaccines are also effective in preventing clinical signs upon infection with virulent NDV, but like the others, do not prevent viral replication (Susta et al, 2015b).…”
Section: Traditional Vaccinesmentioning
confidence: 99%